Change in News Access, Change in Expectations? How Young Social Media Users in Switzerland Evaluate the Functions and Quality of News. (July 2022) - Schwaiger, Lisa; Vogler, Daniel; Eisenegger, Mark
Online media environments have changed the way young people access news. Despite much research on the topic, the expectations of journalistic news by young adults who have turned their back on traditional news media remain unclear. We use a novel multimethod qualitative online study design to investigate the perceived quality, functions, and expectations toward journalistic news of young adults in Switzerland who use social media as their main source for news and rarely consume traditional media. Nineteen young adults between 20 and 25 years of age with different educational levels participated in our study in May 2020. Our results show that even though the participants only occasionally use traditional news media channels, they still consider journalistic news relevant and appreciate quality standards of professional journalism such as actuality and veracity (Swart 2021b). Among the functions of news, the participants highlighted sociability and identification. Exchange and discussion of news are, thus, of high relevance online but also offline. Also, the participants show a high affinity toward news on mobilizing topics, which are of interest to themselves and their peers, and motivate them to engage with news more intensely. According to the participants, news should be attractively prepared, such as with audiovisual formats and easy to understand and integrate into everyday life. The participants also expressed a preference to consume news articles from different media brands within a single platform. Our study outlines a fruitful path for comprehensive qualitative research with innovative online tools.